Use of Design Thinking as Ideas Prototyping Experience in Higher Education - Martins, Amilton R.Q.; Capellari, Márcia; Signori, Glauber; Kalil, Fahad; Spinello, Suellen (Future Studies Research Journal: Trends and Strategies, 2016)
This article presents a case of using Design Thinking in a course of an undergraduate degree. The Design Thinking offers an innovation in thinking, consisting of a cycle of steps comprising inspiration, ideation and implementation. Assuming that it has currently shown on the rise the term innovation together with the large number of startups and the high demand of enterprises to adapt new technologies and create competitive advantages in the environment in which they operate. As experiment we used the Design Thinking in a course of Creativity and Innovation in Undergraduate of Information Systems, running the steps of immersion, design, prototyping and validation, in order to generate non-existent or deficit services ideas that might be offered by third parties in the campus of the college. After the description of the steps of the experiment, are presented some qualitative and quantitative results and future work.